The Experimental Investigation of the Impact Absorption Capability of Piston-Cylinder Air-damper Set-up Perforated with Tiny Holes - A. ENTERIA, NAPOLEON; P. VILLANUEVA, ELISEO (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
An air-damper for impact absorption study was designed and fabricated. It had 32 exit holes, each with a diameter of 5/32 inch. The holes were closed using tin rivet and sealed using grease and insulation tape. The numbers of opened exit holes were varied from 0 to 32 with 17 combinations in horizontal and vertical position. There were three classes of load applied and three trials were done for each opened exit holes position. The theoretical impact was solved using the impact equation and found to be higher compared with impact produced with air-damper. The impact produced and the pressure developed inside the air-damper had a direct relationship in which higher impact produced developed higher pressure inside the damper and vice versa, that is, the impact produced was minimum when large amount of applied energy was absorbed by the escaping air. The position of the opened exit holes also affected the amount of impact produced. The analysis of variance (ANOVA) F test at 0.05 level of significance indicated the significant effect of exit holes opening and position.